Adherence to Medications among Outpatient Adults with Multiple Sclerosis in Medina Province in Ksa (Cross-Sectional Study): Life Sciences-Neuro surgery for better healthcare - Salma Moteb T Al-Mutairi; Hatim Muhammad H Alshalahi; Sara Moteb T Al-Mutairi; Abid M Kareem (International Journal of Life Science and Pharma Research, 2022)
Multiple sclerosis (MS) is a chronic, inflammatory, progressive, demyelinating disease of the central nervous system. Treatment for MS involves long-term disease-modifying therapies (DMTs). Medication adherence in chronic diseases like MS plays an important role in predicting long-term outcomes. This is a cross-sectional, survey-based study was done to assess adherence to medications among adults suffering from MS in Medina Province, Saudi Arabia. The study sample included 90patients diagnosed with multiple sclerosis. These databases contain information about disease presentation, drug prescription, vital status, residency, and role of contact to patient. All the collected data were analyzed by an SPSS program, version 20, and p value < 0.05 was considered significant. A response rate among the MS patients was 97.78%, and their mean age was 36.13±9.58. Most of the participants were above 35 years (55%) and were females. About 37.8% of patients was considered to be adherent to the drugs. The mean total score of BMQ Specific-Necessity was 3.25±0.70 and about 63.4% total score=3 and the mean total score of BMQ Specific-Concerns was (3.34±0.703). About 84.4% total score=3. The mean total score of BMQ General was 3.2727±0.31, and about 81.1% had a total score=3. The mean total score of compliance was 3.2023±0.393.We concluded that many factors affected the patient's adherence to the drug rather than of being dependence to the drugs as worrying about side effects and the cost of the drug.